Assessment of Ovarian Function in the Swamp Buffalo (Bubalus Bubalis) - Abdul Wahab D.V. M., Sharifuddin (1983)
Since ovarian function in the water buffalo (Bubalus bubalis) has received considerable attention, a study was undertaken to: (a) relate ovarian contents to plasma progesterone levels during the oestrous cycle; (b) determine the accuracy of rectal palpation and the plasma progesterone assay for the assessment of ovarian function; and (c) establish the resumption of postpartum ovarian activity. The experimental animals were drawn from a herd of swamp buffaloes, 5-8 years old which had calved between August 1981 and January 1982. For oestrus detection buffaloes were penned and tested daily between 20.00 hrs and 24.00 hrs using a vasectomized buffalo male fitted with a chinball marking device. Ovaries were palpated per rectum or examined by laparoscopy and progesterone levels in plasma were measured by a radioimmunoassay technique. Sixteen cycling buffaloes were subjected to 32 ovarian examinations - laparoscopy and rectal palpation - as well as measurements of plasma progesterone levels. Gross changes in color, size and vasculature permitted the corpus luteum (CL) of the cycle to be graded into four age-dependent categories (CL I-IV) and the rise and fall in plasma progesterone levels reflected the development and regression of the CL. The accuracy of diagnosing ovarian contents by rectal palpation and plasma progesterone levels was determined by examining the ovaries of 68 buffaloes. Thirty-eight (81%) of 47 rectal diagnoses of CL and 26 (90%) of 29 hormonal diagnoses (plasma progesterone levels >0.7 ng/ml of luteal tissue) were confirmed by laparos copy. Seventeen (81%) of 21 rectal diagnoses of no CL and 25 (83%) of 30 hormonal diagnoses of no, luteal tissue were also confirmed. The overall accuracy of diagnosing ovarian function was 81 and 86 percent respectively for rectal palpation and the progesterone assay. Errors were mainly due to the rectal diagnosis of follicles as CL (19%) and the failure of CL to secrete luteal levels of progesterone. Ovarian function in eleven suckled buffaloes were studied from parturition to 150 days postpartum. Plasma progesterone concentrations remained at basal levels during the first 30 days postpartum. An ovulatory cycle was observed in four buffaloes (36%) within 90 days postpartum, in five (45%) between 90 and 150 days postpartum whereas two (18%) animals were acyclic. The intervals from parturition to first ovulation and conception were 89 ± 53 and 112 ± 58 days respectively with an average of 1.4 matings to conceive. Buffaloes with corpora lutea diagnosed by rectal palpation and laparos copy had luteal levels of plasma progesterone. The results of this study showed that rectal palpation should continue as the preferred technique for the diagnosis of ovarian function in the buffalo under field conditions. Progesterone profiles are useful in diagnosing animals which are cycling but not detected in oestrus and animals which are anoestrous or are in early pregnancy. Laparos copy is valuable for a detailed in spection of the ovaries and adnexa. The majority of suckled swamp buffaloes experience a period of postpartum anoestrus of 3 to 4 months duration prior to the resumption of ovarian cyclicity.